(untitled) (Research, Society and Development, 2025)
The objective is to identify the best point for the first puncture, seek to systematize the operation for morbid obesity,and evaluate the anatomical repairs and anthropometric data. In methodology, a prospective, longitudinal quantitative observational study was carried out for 2 years in obese patients with the same surgeon in hospitals in Rio de Janeiro, previously studied and released by a multidisciplinary team. All patients were submitted and asked for informed consent. Patients were selected with a grade III obesity body mass index, included in a questionnaire, with specific data, and measured by the same surgeon. The main and analyzed data were sex, age, BMI, anthropometric measurements such as xiphoid measurement, assessment of the Charpy angle in degrees, and distance from the umbilical scar to the possible puncture. These data were statistically analyzed to identify the best choice for the first puncture or placement of the first trocar. All patients underwent general anesthesia, in the supine position, with legs closed, and using the same technique, intending to visualize and manipulate the hiatus. Anthropometric study and BMI are important data before minimally invasive bariatric surgery, they become important in deciding the placement of the first chamber trocar for better visualization of the upper abdomen, facilitating the surgeon’s work. This standardization according to anthropometry helps and facilitates the management of minimally invasive surgery.